2006
DOI: 10.1016/j.virol.2005.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of evolutionary conserved clustering of bZIP binding sites in the baculovirus homologous regions (hrs) suggests a cooperativity between host and viral transcription factors

Abstract: The genome of the Autographa californica Multinucleocapsid Polyhedrosis Virus (AcMNPV) contains nine interspersed homologous regions (hrs) that function as potent enhancer sequences when linked in cis to either viral or heterologous RNA polymerase II-dependent promoters. Their activity is strongly increased by the binding of the major immediate early viral transregulator IE1 on 28-mer palindromic sites present in hrs. We show that hrs of AcMNPV additionally carry, in the interpalindromic sequences, a large num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…2A). Transient assays revealed that the CRE-like motif functions as a transcriptional activator in AcMNPV (Landais et al 2006). Non-hr replication origins have been reported in some baculoviruses (Habib and Hasnain 2000; Kool et al 1993;Pearson et al 1993;Wu and Carstens 1996).…”
Section: Repeat Regionsmentioning
confidence: 93%
“…2A). Transient assays revealed that the CRE-like motif functions as a transcriptional activator in AcMNPV (Landais et al 2006). Non-hr replication origins have been reported in some baculoviruses (Habib and Hasnain 2000; Kool et al 1993;Pearson et al 1993;Wu and Carstens 1996).…”
Section: Repeat Regionsmentioning
confidence: 93%
“…Although the in vivo origin(s) of baculovirus DNA replication ( oris ) remain unclear, hrs have been implicated as putative oris , and as enhancers of early gene expression using transient replication assays [2325]. In addition, the interpalindromic sequences of baculovirus hrs contain certain cAMP response elements (CRE), which could bind host transcriptions factors of the bZIP family and possibly provide a synergy for the binding of IE-1 to the hrs [26,27]. In other baculovirus genera, particularly some betabaculoviruses, hrs exhibit both spatial and sequence heterogeneity and are devoid of the consensus palidromic sequences such as those found in the type baculovirus AcMNPV.…”
Section: Resultsmentioning
confidence: 99%
“…The sequence contains a conserved late gene TAAG sequence motif, a conserved early gene CAGT motif, two TATA boxes located at -39 bp and -29 bp relative to the transcription start site, two AUG translation start codons, of which the distal one has been proved to be the translation start codon of the pp31 protein in AcMNPV (Guarino and Smith, 1992). In addition, other motifs were also predicted in the sequence, which included CGTGC (Gomi et al, 1999a;Xu et al, 2013), GATA (Kogan and Blissard, 1994;Krappa et al, 1992), and CRE motif (Landais et al, 2006;Rohrmann, 2013) transcription factors ( Fig. 2A).…”
Section: Structural Analysis Of the Bmnpv 39k Promotermentioning
confidence: 98%